Heat distribution over normal and abnormal joints: thermal pattern and quantification. Issue 5 (October 1983) - Salisbury, R S; Parr, G; De Silva, M; Hazleman, B L; Page-Thomas, D P
Abstract : We have identified regular thermal patterns over normal knee, ankle, and elbow joints and demonstrate how synovitis affecting these joints may be identified by alteration or loss of the thermal pattern. Sixty healthy volunteers were thermographed on a total of 190 occasions, and 614 out of 618 joints conformed to the normal thermal pattern. Eighty-five patients with synovitis of at least one of the specified joints were thermographed on a total of 339 occasions, and 322 out of 1362 thermograms were abnormal. No joint with clinical evidence of synovitis had a normal thermal pattern. As temperature-based parameters have been found to show marked diurnal variation and relative frequency distributions do not have this drawback, we suggest that quantification of synovitis by thermography should in future be based on abnormalities of thermal pattern rather than absolute skin temperature values.